Чатал-Гююк и Балканы. Проблемы этнических связей и культурных контактов - Иванов, Вяч. Bc. (1979)
Ivanov, Vjac. Vs.; Çatal-Hüyük and Balkans. Problems of Ethnic Contacts and Cultural Influences; engl. Résumé.